Essentials DT skills - Marshall, Jared; Garner, Simon; Auliffe, Mark; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2003)
This program focuses on skills required to use equipment in design and technology workshops. The program serves as an execellent introduction and is also suitable for reinforcing material covered during classes
Writer, associate producer Simon Garner ; camera , Leigh Tilson ; sound , Wayne Martin
Voice over : Peter Kent
For middle secondary to senior secondary students
Keywords: Solder and soldering; Lathes; Workshops; Technology